Strict Product Liability of Medical Employees for Damage Caused by the Use of Medical Means with Deficiency in the USA Law - Samir MANIĆ; Sabina ZEJNELAGIĆ (Tehran University of Medical Sciences, 2018)
Strict Product Liability of Medical Employees for Damage Caused by the Use of Medical Means with Deficiency in the USA Law